The European Ocean Observing Community: urgent gaps and recommendations to implement during the UN Ocean Decade - Hassoun, Abed El Rahman; Tanhua, Toste; Lips, Inga; Heslop, Emma; Petihakis, George; Karstensen, Johannes (Frontiers in Marine Science, 2024)
The interdisciplinary community of ocean and coastal observers and modelers in Europe is driven by national observing needs for prediction and management of intricate processes shaping Europe’s Seas. Not all observing needs can be addressed by nations alone and various coordination activities exist to overcome fragmentation and create cross benefit within the European Ocean Observing Community (EOOC). This way critical insights into impacts of climate change on European Waters and cross border marine resources management can be achieved. Based on a large number of published material, this article is identifying and addressing the current state of activities of the EOOC and states gaps that potentially prevent efficacy. Key challenges include spatial and temporal coverage in observations, data integration, accessibility, uncertainties in projections, technological hurdles, and engagement and communication gaps. Detailed recommendations are provided for identified gaps, offering valuable insights for stakeholders, funders, and supporters of the EOOC. These recommendations, extending beyond academic interest, carry significant implications for climate change mitigation, marine resource management efficiency, ecosystem resilience, disaster preparedness, economic benefits, and the broader scientific advancements in European marine science, thereby benefiting society at large. As the world undergoes transformative changes impacting all facets of European life, substantial investment and support for the EOOC are crucial for precise information, accurate predictions, supporting sustained services that contribute to business growth and community resilience, and a sustainable ocean.